Australian Aboriginal Birth Cohort study: follow-up processes at 20 years - Davison Belinda; Jamieson Lisa; Gunthorpe Wendy; Lawrance Megan; Mackerras Dorothy; Singh Gurmeet; Sayers Susan; Schutz Kobi; Fitz Joseph (BMC, 2009)
Abstract Background In 1987, a prospective study of an Australian Aboriginal Birth Cohort was established focusing on the relationships of fetal and childhood growth with the risk of chronic adult disease. However as the study is being conducted in a highly marginalized population it is also an important resource for cross-sectional descriptive and analytical studies. The aim of this paper is to describe the processes of the third follow up which was conducted 20 years after recruitment at birth. Methods Progressive steps in a multiphase protocol were used for tracing, with modifications for the expected rural or urban location of the participants. Results Of the original 686 cohort participants recruited 68 were untraced and 27 were known to have died. Of the 591 available for examination 122 were not examined; 11 of these were refusals and the remainder were not seen for logistical reasons relating to inclement weather, mobility of participants and single participants living in very remote locations. Conclusion The high retention rate of this follow-up 20 years after birth recruitment is a testament to the development of successful multiphase protocols aimed at overcoming the challenges of tracing a cohort over a widespread remote area and also to the perseverance of the study personnel. We also interpret the high retention rate as a reflection of the good will of the wider Aboriginal community towards this study and that researchers interactions with the community were positive. The continued follow-up of this life course study now seems feasible and there are plans to trace and reexamine the cohort at age 25 years.